Lattice ordered interval-valued hesitant fuzzy soft sets in decision making problem - Pandipriya, Ar.; Vimala, J.; Sabeena Begam, S. (International Journal of Engineering and Technology, 2017)
In 2015, Haidong Zhang enhanced the idea of Hesitant Fuzzy Sets and Soft Sets into Interval-Valued Hesitant Fuzzy Soft Sets along with its properties. In this present work, we establish the Lattice Ordered Interval-Valued Hesitant Fuzzy Soft Sets and examined its vital properties with examples. Eventually the application of Lattice Ordered Interval-Valued Hesitant Fuzzy Soft Set to decision making problem is established by means of elegant algorithm.